Development of a Mathematics Curriculum with a Financial Numeracy Approach Based on Local Wisdom - Nur Maulidiawati Rahman; Sirwanti Sirwanti; Hirpan Hirpan (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
This study explores the integration of financial numeracy with local wisdom in mathematics education in Indonesia. By incorporating real-life financial scenarios, such as budgeting, saving, and investment calculations, into mathematics lessons, the research aims to enhance students' understanding of mathematical concepts while simultaneously improving their financial literacy. The study also emphasizes the importance of using local cultural and economic knowledge as a context for learning, making abstract mathematical concepts more relevant and accessible. The findings suggest that contextualizing mathematics education through local wisdom significantly improves student engagement, understanding, and practical application of mathematical knowledge. The integration of financial numeracy helps students make informed financial decisions and prepares them for future financial challenges. This research contributes to the development of a mathematics curriculum that combines financial literacy with local context, offering a more inclusive, relevant, and practical approach to education. The study’s findings contribute to the ongoing development of more inclusive, relevant, and practical educational frameworks that incorporate financial literacy into the mathematics curriculum.